A new species of Caloptilia (Lepidoptera: Gracillariidae) from Japan and Korea - Yagi, Sadahisa; Goto, Kiyoshiro; Sohn, Jae-Cheon (Zootaxa, 2024)
A new species of Caloptilia, C. rhynchosiae n. sp. is described, based on 16 specimens from Japan and Korea. The species is characterized by the presence of the saccular process in the male genitalia. A fabaceous vine, Rhynchosia tomentosa (L.) Hook. & Arn. is reported as the larval host of C. rhynchosiae n. sp. Larval feeding preference, biology and pupation process are described for the species. The species turned out to be host-specific. Two sets of COI barcodes were generated for C. rhynchosiae n. sp. The genetic distances of COI barcodes between the new species and other congeners in the public databases are compared. The conclusion was made that C. rhynchosiae n. sp. was misidentified as C. soyella in the BOLD and GenBank DNA barcode depositories.